2022
DOI: 10.3389/fgene.2022.931580
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide characterization of the NLR gene family in tomato (Solanum lycopersicum) and their relatedness to disease resistance

Abstract: Nucleotide-binding leucine-rich-repeat receptors (NLR), the largest group of genes associated with plant disease resistance (R), have attracted attention due to their crucial role in protecting plants from pathogens. Genome-wide studies of NLRs have revealed conserved domains in the annotated tomato genome. The 321 NLR genes identified in the tomato genome have been randomly mapped to 12 chromosomes. Phylogenetic analysis and classification of NLRs have revealed that 211 genes share full-length domains categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…To further explore how defense processes might be involved in the incompatible response, we targeted NLRs and downstream molecular signaling involved in defense for deeper analysis. Using a collection of 320 previously annotated tomato NLRs (Bashir et al ., 2022), we identified 97 defense-related receptors that were significantly upregulated in incompatible grafts (Fig. 6c, Table S12).…”
Section: Resultsmentioning
confidence: 99%
“…To further explore how defense processes might be involved in the incompatible response, we targeted NLRs and downstream molecular signaling involved in defense for deeper analysis. Using a collection of 320 previously annotated tomato NLRs (Bashir et al ., 2022), we identified 97 defense-related receptors that were significantly upregulated in incompatible grafts (Fig. 6c, Table S12).…”
Section: Resultsmentioning
confidence: 99%
“…There was very high discrepancy and fluctuation among the reported literature studies for the number of TNLs present in tomatoes. For example, Qian et al (2017), Andolfo et al (2013Andolfo et al ( , 2014 and Bashir et al (2022) reported different numbers for full length TNLs in tomatoes with the maximum count reaching twenty-six. This discrepancy perhaps arose due to the nature of the work being carried out with more emphasis on the in-silico genome wide identification of all the NBS-LRRs and less focus was placed on the TNLs.…”
Section: Discussionmentioning
confidence: 99%
“…However, elaboration upon role of TNL members under biotic stress was almost negligible in such reports. A recent report on genome wide identification of NLRs (NBS-LRR receptors) identified the TNL repertoire, yet, an expression analysis was lacking for these genes (TNLs) for early blight disease as well as for other biotic stresses (Bashir et al 2022). Thus, in the present work, after identifying the TNL gene family members, they were assessed by protein-protein interaction prediction and expression analysis using RNA-Seq data for the spatio-temporal expression and biotic stresses.…”
mentioning
confidence: 98%
“…They represent the major class of intracellular innate immune receptors and the most represented group of resistance genes. To date, several NBS–LRR resistance genes and quantitative trait loci (QTLs) for plant resistance to pathogens were mapped in plants, some of which were also cloned [ 24 , 25 ], and, in many cases, a co-localization between QTLs and genes was highlighted. This made it possible to identify candidate genes and to develop molecular markers for plant resistance [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, several NBS–LRR resistance genes and quantitative trait loci (QTLs) for plant resistance to pathogens were mapped in plants, some of which were also cloned [ 24 , 25 ], and, in many cases, a co-localization between QTLs and genes was highlighted. This made it possible to identify candidate genes and to develop molecular markers for plant resistance [ 24 , 25 ]. In cannabis, the involvement of NLRs in gene-for-gene interaction with PM has been recently demonstrated [ 18 ].…”
Section: Introductionmentioning
confidence: 99%